FORECASTING THE SPATIAL DYNAMICS OF THE EPIZOOTIC PROCESS PLAGUE AMONG THE WILD ANIMALS IN THE DESERT PLAGUE FOCI OF KAZAKHSTAN FOR THE PERIOD 2020-2024. BASED ON GIS TECHNOLOGIES - Abdel, Z.Zh.; Zhumadylova, Z.B.; Aikimbayev, A.M.; Tokmurziyeva, G.Zh.; Mussagaliyeva, R.S.; Abdirassilova, A.A.; Issayeva , S.B.; Baitursyn, B.A.; Dalibayev, Zh.S.; Abdeliyev, B.Z.; Begimbayeva, E.Zh.; Shayakhmetov, A.M.; et al. (Eurasian Journal of Applied Biotechnology, 2025)
The present study is aimed at spatial and temporal analysis and prediction of the epizootic process of plague infection among wild animals in desert natural plague foci of the Republic of Kazakhstan using geoinformation modeling methods. The data of epizootological monitoring for 2020–2024 were used as the initial base, including information on the abundance and distribution of the main reservoir species (Rhombomys opimus), vector activity (ectoparasites), as well as climatic, landscape and anthropogenic characteristics of the studied territories. Spatial data was processed and visualized using the ArcGIS and QGIS software platforms. Situational, analytical, and predictive electronic maps of epizootic activity have been constructed. By the modeling results, it was found that in the future, epizootic activity is most likely to increase in the western parts of the desert zone of Kazakhstan, including in the North Aral, Volga-Ural sandy, Predustyurt and Ustyurt foci. A potential increase in risk is also expected in the Betpakdalinsky, Moyinkumsky and Dariyalyk-Takyr autonomous foci. Under the conditions of predicted climatic changes, the probability of expanding the circulation zones of the plague pathogen may increase, which increases the risk of infection of humans and camels in enzootic territories. The research results have high applied significance and can be used to optimize epizootological surveillance systems, plan preventive and anti-epidemic measures, and minimize the risk of transmission of plague infection from animals to humans.